Validation and development of an instrument: Level of knowledge for the diagnosis and treatment of dengue fever in Lambayeque region - Paico-Romero, Claudia (2012)
Objectives: To validate an instrument for determining the knowledge status with respect to the diagnosis and treatment to be used by general practitioners when facing cases of dengue fever. Material and Method: This is a descriptive and cross-sectional study. We performed a pilot study with 30 physicians for validating the instrument. The final questionnaire had 16 questions. The sample included 115 primary health care facilities and emergency services in hospitals in Lambayeque region. The statistical analysis was performed using absolute and relative rates, chi-square, and ANOVA. Results: When validating the instrument, a Cronbach 0,804 alpha value (>0,8) was found; and the 16-item correlations were 0,438 and 0,852. With respect to the validity of contents, experts assigned 3,5/5 values for pertinence and clarity scores. In construct validity, the Kaiser-Meyer- Olkin score for sample adequacy was 0,082, and the Bartlett's sphericity test value was 0,023. We found that 50,4 % of interviewed physicians had a low level of knowledge with respect to diagnosis and management of dengue fever cases; 48,7 % had a midline knowledge level, and only 0,9% had a good level with respect to diagnosing and managing cases of dengue fever. These findings were associated with prior training and years being in practice (p <0,05). Conclusions: There is a low level of knowledge in Lambayeque region physicians with respect to the diagnosis and treatment of dengue fever cases, and there is an association between this and the prior training history and years being in practice.